2009
DOI: 10.1007/s00348-009-0661-2
|View full text |Cite|
|
Sign up to set email alerts
|

Experimental investigation of some aspects of insect-like flapping flight aerodynamics for application to micro air vehicles

Abstract: Insect-like flapping flight offers a power-efficient and highly-manoeuvrable basis for micro air vehicles for indoor applications. Some aspects of the aerodynamics associated with the sweeping phase of insect wing kinematics are examined by making particle image velocimetry measurements on a rotating onebladed propeller immersed in a tank of seeded water. The work is motivated by the paucity of data with quantified error on insect-like flapping flight, and aims to fill this gap by providing a detailed descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 39 publications
(54 reference statements)
2
18
0
Order By: Relevance
“…[2][3][4][5] But the interest in the unsteady aerodynamics of flapping flight has significantly grown in recent years in relation to the design of Micro-Aerial Vehicles (MAVs) that take advantage of the accumulated knowledge on animal flight. [6][7][8][9][10] Here, we focus on the thrust generation by an oscillating airfoil at low Reynolds numbers, particularly on the characterization of the vortical flow structures responsible for the maximum thrust efficiency at selected non-dimensional frequencies and amplitudes of the oscillations. We consider the two-dimensional (2D) and incompressible viscous flow around a plunging airfoil at different mean angles of attack.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] But the interest in the unsteady aerodynamics of flapping flight has significantly grown in recent years in relation to the design of Micro-Aerial Vehicles (MAVs) that take advantage of the accumulated knowledge on animal flight. [6][7][8][9][10] Here, we focus on the thrust generation by an oscillating airfoil at low Reynolds numbers, particularly on the characterization of the vortical flow structures responsible for the maximum thrust efficiency at selected non-dimensional frequencies and amplitudes of the oscillations. We consider the two-dimensional (2D) and incompressible viscous flow around a plunging airfoil at different mean angles of attack.…”
Section: Introductionmentioning
confidence: 99%
“…This issue was investigated in a previous study by Ansari et al [8], in which the conclusions drawn also apply here because the same rig was used in both cases. In their study, the flow velocities following a wing rotation were measured to observe how the fluid settled, which is illustrated in Fig.…”
Section: Settling Timementioning
confidence: 83%
“…It was found that this induced flow velocity was essentially zero, and therefore, the seeding response error was assumed to be negligible. This evaluation of the seeding response error is described in greater detail in [8].…”
Section: A Seeding Responsementioning
confidence: 99%
See 2 more Smart Citations